Pengaruh Faktor Individual Dan Situational Terhadap Niat Whistleblowing - Febby Chika Putri Mulfag; Vanica Serly (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to look at individual and situational factors that influence the intention of civil servants to conduct whistleblowing, especially for civil servants not in the Regional Finance Agency of West Sumatra Province. Individual factors consist of three main factors, namely attitudes towards whistle-blowing, subjective norms, and perceived behavioral control and three main factors on situational factors, namely seriousness of errors, wrongdoing status, and personal reporting costs. This study uses a semi-experimental method with a quantitative approach. The research sample was determined by purposive sampling which consisted of 56 employees. This study found that individual and situational factors succeeded in predicting whistle-blowing intentions. In particular, the results of the study show that there are six antecedents of whistleblowing intentions between civil servants who do not have positions in BAKEUDA: attitudes towards whistle-blowing, subjective norms, perceived behavioral control, seriousness of errors, wrongdoing status, and personal reporting costs